Analysis of learning components in implementation of educational process in schools - Azka Widhiasti; Anggie Putri; Muhammad Adnan Fanani; Najwa Salim; Yandhy Rizky Kurnia (Universitas Pendidikan Indonesia, 2022)
Indonesian education has undergone many changes in line with the changes in the applied curriculum. This affects educators in carrying out teaching and learning activities so that they must quickly adapt to implementing the new curriculum, provide understanding to students, and guide them to adapt to the system. When the curriculum changes, the essential things in learning also change according to the change in curriculum, namely the learning components. Learning in its process has elements that are related and influence each other. The learning component includes objectives, materials, media, strategies, and evaluation. As time goes by and changes in technology, aspects of learning components change into a form of adjustment. Elements of the learning component turned into a state of adjustment. This study aims to look back at the learning components when the new curriculum is implemented in schools. The research method uses qualitative methods with library research. The result of this study is that the learning components when the new curriculum is implemented have some differences in the application of aspects of the learning components. Abstrak Pendidikan Indonesia sudah mengalami banyak perubahan seiring dengan bergantinya kurikulum yang diterapkan. Hal ini berpengaruh pada pendidik dalam melaksanakan kegiatan belajar mengajar sehingga harus cepat beradaptasi melaksanakan kurikulum baru dan memberi pengertian kepada peserta didik serta menuntun mereka untuk dapat beradaptasi dengan sistem. Pada saat perubahan kurikulum hal penting dalam pembelajaran ikut berubah menyesuaikan pergantian kurikulum, yaitu komponen pembelajaran. Pembelajaran dalam prosesnya memiliki komponen-komponen yang terkait satu sama lain dan saling mempengaruhi. Komponen pembelajaran terdiri atas tujuan, materi, media, strategi, dan evaluasi. Seiring berjalannya waktu dan perubahan teknologi, aspek dari komponen pembelajaran berubah sebagai bentuk penyesuaian. Aspek dari komponen pembelajaran berubah sebagai bentuk penyesuaian. Penelitian ini bertujuan untuk melihat kembali komponen pembelajaran saat diterapkannya kurikulum baru di sekolah. Metode penelitian menggunakan metode kualitatif dengan studi kepustakaan. Hasil dari penelitian ini adalah komponen pembelajaran saat kurikulum baru diterapkan memiliki beberapa perbedaan dalam menerapkan aspek-aspek dari komponen pembelajaran. Kata Kunci: bahan ajar; evaluasi pembelajaran; komponen pembelajaran; media pembelajaran; strategi pembelajaran; tujuan pembelajaran